Allelopathic effect of sunflower water extract on the germination of soybean and hairy beggartick - Corsato, Jaqueline Malagutti [UNESP]; Fortes, Andréa Maria Teixeira [UNESP]; Santorum, Márcia [UNESP]; Leszczynski, Raquel [UNESP] (Universidade Estadual de Londrina, 2010)
The aim of this work was to evaluate the allelopathic effect of water extract from sunflower fresh leaves on the germination and initial development of conventional and transgenic soybean cultivars, and of the invasive hairy beggartick (Bidens pilosa L.). Experiments were carried out at Laboratory of Plant Physiology, Universidade Estadual do Oeste do Paraná, in 2007. Fresh leaves from sunflower were ground in a blender at the proportion 200g/1L distilled water, resulting in crude extract (100%), in which pH was measured. Dilutions of 80%, 60%, 40% and 20% were done from the crude extract, and only distilled water was used as control. Statistical analysis (Tukey 5% probability) indicated that only the highest extract concentrations (60%, 80% and 100%) influenced the analyzed parameters for conventional and transgenic soybean. Beggartick seeds, however, had germination percentage completely inhibited when 40% water extract was applied, which indicates that sunflower straw could be used as a natural herbicide. Nevertheless, field studies must be carried out to prove such effect.
Efeito alelopático do extrato aquoso de folhas de girassol sobre a germinação de soja e picão-preto
Keywords: Allelopathy; Bidens pilosa L; Glycine max (L.) Merrill; Helianthus annus L.